1989
DOI: 10.1002/pros.2990140404
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of androstenedione‐induced prostate growth in intact beagle dogs by a combined treatment with the antiandrogen cyproterone acetate and the aromatase inhibitor 1‐methyl‐androsta‐1,4‐diene‐3,17‐dione (1‐methyl‐ADD)

Abstract: Interference with estrogenic and androgenic actions might result in an inhibitory effect of benign prostatic hyperplasia (BPH). In the present study the effects of the treatment of intact, adult beagle dogs with the antiandrogen cyproterone acetate (CPA) and the aromatase inhibitor 1-methyl-ADD either alone or in combination on androstenedione-induced prostate growth and on testes, epididymides, and the pituitary was investigated. 1-Methyl-ADD induced a marked counterregulatory increase in the serum testostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Unlike similar effects in this model with the steroidal AI exemestane, our previous study [30] showed these bone preserving effects are not blocked by the androgen receptor blocker flutamide [33] and thus appear to be non-androgenic [4,30,34,35]. The mechanism of bone preserving effects of ATA remains unexplained.…”
Section: Discussionmentioning
confidence: 53%
“…Unlike similar effects in this model with the steroidal AI exemestane, our previous study [30] showed these bone preserving effects are not blocked by the androgen receptor blocker flutamide [33] and thus appear to be non-androgenic [4,30,34,35]. The mechanism of bone preserving effects of ATA remains unexplained.…”
Section: Discussionmentioning
confidence: 53%
“…Administration of a 5a-reductase inhibitor, ®nasteride, and an aromatase inhibitor, arimidex, resulted in a signi®cant increase in prostate volume, accompanied by a 3-to 10-fold increase in serum testosterone levels and a signi®cant increase in testicular volume. In connection with the synergistic effects of Atamestane and antiandrogen cyproterone acetate (CPA), it would appear that CPA in combination with Atamestane induced a selective and complete inhibition of the androgenic effects at the level of the prostate, while CPA did not negatively in¯uence the function of the testis, the epididymidis or the pituitary (45). These experimental ®ndings demonstrated that estrogen deprivation with antiandrogen might represent a useful treatment for human BPH.…”
Section: Discussionmentioning
confidence: 88%
“…ATA significantly increased BMD, bone mechanical strength and trabecular bone volume in OVX rats. But these bone preserving effects are not blocked by the androgen receptor blocker flutamide (FLT) [38] and thus appear to be non-androgenic [2,39,40]. ATA had no stimulatory effect on the uterine epithelium in OVX rats indicating an absence of an intrinsic estrogenic signal.…”
Section: Discussionmentioning
confidence: 99%